Rhizarian 'Novel Clade 10' Revealed as Abundant and Diverse Planktonic and Terrestrial Flagellates, including Aquavolon n. gen. (14th May 2018) - Bass, David; Tikhonenkov, Denis Victorovich; Foster, Rachel; Dyal, Patricia; Janouškovec, Jan; Keeling, Patrick J.; Gardner, Michelle; Neuhauser, Sigrid; Hartikainen, Hanna; Mylnikov, Alexandre P.; Berney, Cédric
Abstract: Rhizarian 'Novel Clade 10' (NC10) is frequently detected by 18S rRNA gene sequencing studies in freshwater planktonic samples. We describe a new genus and two species of eukaryovorous biflagellate protists, Aquavolon hoantrani n. gen. n. sp. and A. dientrani n. gen. n. sp., which represent the first morphologically characterized members of NC10, here named Aquavolonida ord. nov. The slightly metabolic cells possess naked heterodynamic flagella, whose kinetosomes lie at a right angle to each other and are connected by at least one fibril. Unlike their closest known relative Tremula longifila, they rotate around their longitudinal axis when swimming and only very rarely glide on surfaces. Screening of a wide range of environmental DNA extractions with lineage‐specific PCR primers reveals that Aquavolonida consists of a large radiation of protists, which are most diversified in freshwater planktonic habitats and as yet undetected in marine environments. Earlier‐branching lineages in Aquavolonida include less frequently detected organisms from soils and freshwater sediments. The 18S rRNA gene phylogeny suggests that Aquavolonida forms a common evolutionary lineage with tremulids and uncharacterized 'Novel Clade 12', which likely represents one of the deepest lineages in the Rhizaria, separate from Cercozoa (Filosa), Endomyxa, and Retaria.